Threat of justice: truth and norm - Андреевич Исаев, Игорь (Studia Iuridica Toruniensia, 2018)
The Article is devoted to one of the most fundamental problems of the philosophy of law – the interaction of government and law in the broad sense of the word in the search for truth, so important for the governing and the governed. In the framework of a larger policy the regulation is constantly faced with the force of authoritarianism, giving rise to forms of lawful and unlawful ruling. Religious and ontological values interact with the processes of secularization, when the policy comes out from under the control of moral principles. In this situation, even justice, the most important criterion of morality and law, may be not only relative, but also a dangerous factor. The extent and mechanisms of modern societies, as it seems, are the slopes for such a transformation.